2017
DOI: 10.3851/imp3219
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Non-Adherence to HBV Antiviral Therapy

Abstract: Background: Hepatitis B virus (HBV) anti-viral therapy has the potential to reduce the burden of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 46 publications
(80 reference statements)
1
8
0
3
Order By: Relevance
“…However, different adherence rates for chronic HBV treatment was found in the previous published literature. On the one hand a high adherence rate of 81-99% were reported in the systemic review of Lieveld et al [15], but on the other hand, a lower adherence rate of about 75% was found in the recently published literature, including original studies and systemic review and meta-analysis [16,17]. These differences can be accounted by the varying methods of adherence assessment used in the different studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, different adherence rates for chronic HBV treatment was found in the previous published literature. On the one hand a high adherence rate of 81-99% were reported in the systemic review of Lieveld et al [15], but on the other hand, a lower adherence rate of about 75% was found in the recently published literature, including original studies and systemic review and meta-analysis [16,17]. These differences can be accounted by the varying methods of adherence assessment used in the different studies.…”
Section: Discussionmentioning
confidence: 99%
“…Хотя необходимо отметить, что средний возраст пациентов, получавших телбивудин, был достоверно ниже (35±12 лет) такового больных, принимавших тенофовир (43±13 лет) и энтекавир (44±14 лет). В ряде работ показано, что приверженность к терапии в среднем ниже у больных молодого возраста [32,39]. В связи с этим лицам молодого возраста необходимо чаще и более детально объяснять необходимость регулярного приема препарата, рекомендовать использование технических устройств для напоминания о времени приема препарата.…”
Section: Discussionunclassified
“…Показано также, что приверженность к лечению, как правило, снижается при увеличении длительности терапии [36,37]. Среди других факторов, ассоциирующихся с приверженностью к терапии, выделяют уровень материального благополучия и образования пациента, количество других принимаемых лекарственных средств, степень взаимодействия врача и пациента [32,35,38,39]. В исследовании Peng и соавт.…”
Section: Discussionunclassified
“…Poor patient knowledge (lack of appropriate disease and medicines education); low health literacy (poor understanding of sequelae); cultural and personal beliefs about illness, medications, and health care professionals ("doctors overuse medications," "medications are not helpful or safe"); and the undesirable stigma surrounding liver disease may also impact patients' ability or confidence to engage with health services to obtain treatment. (17,(23)(24)(25)(26) This is particularly important in the management of viral hepatitis as nonadherence can lead to viral resistance, treatment failure, and increased risk of developing cirrhosis.…”
Section: Knowledge Beliefs and Medication Management Behaviormentioning
confidence: 99%